HUBUNGAN MASA KERJA, LAMA KERJA, LAMA PENYEMPROTAN DAN FREKUENSI PENYEMPROTAN TERHADAP KADAR KOLINESTERASE DALAM DARAH PADA PETANI DI DESA SUMBEREJO KECAMATAN NGABLAK KABUPATEN MAGELANG - Fitrisya Lucki Dwiyanti; Yusniar Hanani Darundiati; Nikie Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2018)
The high use of pesticides on farmers in Sumberejo village and exposure to pesticides for a long time can accumulate in the body to affect blood cholinesterase levels. Low cholinesterase levels indicate pesticide poisoning. The purpose of this study was to determine the relationship between length of service, duration of work, duration of spraying and spraying frequency with blood cholinesterase activity on farmers in the Sumberejo village. The type of research used is observational analytic with cross sectional approach. Data were obtained through interviews using questionnaires and blood cholinesterase level examination. Data were analyzed using Spearman rank correlation test. The variables observed were period of work, duration of work, duration of spraying, frequency of spraying, and blood cholinesterase levels. The average cholinesterase level of respondents was 7146.7 U / L. The result of statistical test showed that there was correlation between length of service(p = 0,008) and spraying frequency (p = 0,026) to cholinesterase level. Duration of work (p = 0,526) and duration of Spraying (p = 0,678) did not show any association with cholinesterase level. The conclusion of this study is that there is a relationship between the working period and the frequency of spraying with cholinesterase levels, there is no relationship between the length of work and spraying with cholinesterase